2020
DOI: 10.3389/fonc.2020.564889
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Distance From the Subventricular Neural Stem Cell Niche Does Not Correlate With Survival

Abstract: ObjectiveTo determine the relationship between survival and glioblastoma distance from the ventricular-subventricular neural stem cell niche (VSVZ).Methods502 pre-operative gadolinium-enhanced, T1-weighted MRIs with glioblastoma retrieved from an institutional dataset (n = 252) and The Cancer Imaging Atlas (n=250) were independently reviewed. The shortest distance from the tumor contrast enhancement to the nearest lateral ventricular wall, the location of the VSVZ, was measured (GBM-VSVZDist). The relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Our study showed that SVZ involvement is a negative prognostic factor of PFS for older IDH-wild-type glioblastoma in univariate and multivariate analyses and an unfavourable prognostic factor of OS in univariate analysis but not an independent prognostic factor of OS in multivariate analysis. Mistry et al [ 62 ] analysed the relationship between the distance to the lateral ventricular wall from glioblastoma and the survival outcome of 502 glioblastoma patients, and the results showed a significantly decreased overall survival only when glioblastoma contacted the lateral ventricular wall. OS did not correlate with distance to the lateral ventricular wall from glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that SVZ involvement is a negative prognostic factor of PFS for older IDH-wild-type glioblastoma in univariate and multivariate analyses and an unfavourable prognostic factor of OS in univariate analysis but not an independent prognostic factor of OS in multivariate analysis. Mistry et al [ 62 ] analysed the relationship between the distance to the lateral ventricular wall from glioblastoma and the survival outcome of 502 glioblastoma patients, and the results showed a significantly decreased overall survival only when glioblastoma contacted the lateral ventricular wall. OS did not correlate with distance to the lateral ventricular wall from glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria were as follows: i) All the cases were solitary lesions and pathologically diagnosed as glioma (2016 WHO classification of tumors of the central nervous system ( 3 )); ii) both the first and second operations were performed in Qilu Hospital; iii) cranial MRI was performed after the first operation with detection of enhanced new lesions, or >25% larger than before, iv) the expected survival time was >8 weeks and v) the Karnofsky score (KPS) was >60( 26 ). Patients with irradiation necrosis were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due to the fact that NSCs in SVZ can leave the niche and migrate over long distances to promote tumor relapse, and GBM exposed to SVZ are closely related to cerebrospinal fluid, which circulates and spreads tumor cells to distant locations [ 25 ]. Studies have shown that GBM patients exposed to SVZ have a higher expression rate of CD133 (a GBM biomarker related to radiation resistance expressed by both NSCs and GSCs) than those not exposed [ 36 , 38 40 ]. Therefore, CD133 expression by NSCs in SVZ may be a factor in the high recurrence and poor prognosis of GBM.…”
Section: The Role Of Svz Neural Stem Cell Niche In Gbmmentioning
confidence: 99%